The day-of-the-week effect on stock market returns volatility : South African context - Lameck, Niyoshaka Nistlaba Stanley (My University, 2016)
Volatility of returns is an important parameter in reaching financial decisions among investors. As such, a concise understanding of returns volatility trends could help in predicting stock price. A study was undertaken to examine the existence of the variations in volatility of stock returns by the day of the week referred to as the day-of-the-week effect on returns volatility and how the effect has evolved during three five-year sub-periods on the Johannesburg Securities Exchange (JSE). Data for the JSE Top 40, Mid Cap and Small Cap indices from 1996 to 2010 were used for the study. The variations of mean returns and returns volatility were examined. Monday was observed to be highest mean returns day for the JSE Top 40 and Friday for JSE Mid Cap and JSE Small Cap. Tuesday was the lowest mean returns day for all the three indices. Monday and Thursday’s day-of-the-week effect on returns was detected for the JSE Top 40 and on Thursday and Friday for the JSE Mid Cap and JSE Small Cap at the 1% confidence level. The Monday, Wednesday, Thursday and Friday day-of-the-week effects are present for JSE Mid Cap and the Wednesday day-of-the-week effect for the JSE Small Cap at 5% confidence level. Thursday has the highest returns volatility for the JSE Top 40. The JSE Mid Cap and JSE Small Cap have their highest returns volatility on Wednesday and Monday respectively. For all the indices, Fridays have the lowest returns volatility. The presence of the day-of-the-week effect in returns volatility was observed for the JSE Small Cap. The results do not show a strong effect in the JSE Top 40 returns volatility, whereas the effect is insignificant for the JSE Mid Cap index. For the 1996 to 2000, 2001 to 2005 and 2006 to 2010 sub-periods, their respective highest mean returns day are Thursday, Tuesday and Monday and lowest mean returns days are Monday, Thursday and Friday. The day-of-the-week effect in mean returns was detected for Wednesday and Friday at 1% for the 2001 to 2005 sub-period and on Tuesday, Wednesday and Friday at 5% for 2006 to iii 2010. The day-of-the-week effect was not detected in the 1996 to 2000 sub-period in mean returns. The highest and lowest returns volatility days for 1996 to 2000 are Monday and Friday respectively. The respective highest and lowest returns volatility days are Friday and Thursday for 2001 to 2005 and Friday and Monday for 2006 to 2010. For 1996 to 2000, the day-of-the-week effect in returns volatility was only observed on Friday at the 1% confidence level and on Monday and Thursday at the 10% confidence level. For the 2001 to 2005 and 2006 to 2010 sub-periods, the effect was statistically insignificant at the 10%confidence level. The day-of-the-week effect on returns volatility for JSE Top 40 for the sub-periods studied has shown to disappear on the South African JSE. Given that apart of Friday, the effect for Monday and Thursday for 1996 to 2000 was only significant at the 10% confidence level, this suggests a very weak effect on the two days.
MBA
Keywords: Johannesburg Stock Exchange. Stocks -- South Africa -- Rate of return. Stock price forecasting -- South Africa.